2022
DOI: 10.1007/s11540-021-09538-5
|View full text |Cite
|
Sign up to set email alerts
|

Protein Quality of South African Potatoes to Inform Dietary Choices

Abstract: Protein content was determined using both the nitrogen to protein conversion factor of 6.25 and the summation of amino acids for four of the potato cultivars (Solanum tuberosum L.) most commonly consumed in South Africa. Protein content for the cultivars varied between 1.65 g/100 g and 2.14 g/100 g fresh-weight when using protein conversion and 1.64 g/100 g and 2.14 g/100 g when using the sum of amino acids. Significant differences were found between the amino acid contents of the different cultivars. Leucine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…These suggested that the unsuitable mixed proteins could not meet the growth requirements of fish. Normally, it is considered that dietary EAAI is important of the protein quality [37]. In the present study, the growth performance of different diets was different though similar dietary EAAI were composed.…”
Section: Discussionmentioning
confidence: 68%
“…These suggested that the unsuitable mixed proteins could not meet the growth requirements of fish. Normally, it is considered that dietary EAAI is important of the protein quality [37]. In the present study, the growth performance of different diets was different though similar dietary EAAI were composed.…”
Section: Discussionmentioning
confidence: 68%
“…The total protein content of potato tubers is relatively low (1.0-3.0% FW or 5.0-14.0% DW) but comparable to cereals on a dry basis and better than commonly consumed vegetables 3 . Potato protein has high biological activity due to its high free amino acid score (69.0-76.0%) 4,5 and higher nutritional value than other commonly consumed plant sources due to its high content of essential amino acids 6 . Potato contains all nine essential amino acids 3 , qualitatively superior to many other plant-based proteins 7 .…”
mentioning
confidence: 99%